2020
DOI: 10.1145/3433148.3433154
|View full text |Cite
|
Sign up to set email alerts
|

Why Is It Hard to Fight Herding?

Abstract: The ubiquity of information, in part a consequence of the fast growth of Internet technologies, provides individuals with previously unknown opportunities to acquire and share information about new technology products. We witness numerous situations where potential adopters observe the decisions (but not the reasoning) of others and imitate their adoption behaviors. This implies that herd behavior can lead to en mass adoption. However, individuals possessing different characteristics exhibit different degrees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…Herd mentality is measured by three items adapted from Darban and Polites (2020). The items used include “When many people buy in a cross-border integrated supermarket, it will prompt me to want to buy products in different formats,” “When friends and others are recommending, it will prompt me to want to buy products of different formats,” and “When there is a lot of related social media and advertising, it will prompt me to want to buy products in different formats.”…”
Section: Research Methodology and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Herd mentality is measured by three items adapted from Darban and Polites (2020). The items used include “When many people buy in a cross-border integrated supermarket, it will prompt me to want to buy products in different formats,” “When friends and others are recommending, it will prompt me to want to buy products of different formats,” and “When there is a lot of related social media and advertising, it will prompt me to want to buy products in different formats.”…”
Section: Research Methodology and Designmentioning
confidence: 99%
“…Faced with the unfamiliar, consumers tend to refer to the buying opinions of other people before making a decision in order to both eliminate incomplete information and reduce the uncertainty of choice as well as reduce the effort of searching for information (Chen et al, 2021; He et al, 2021). Darban and Polites (2020) empirically researched users’ adoption of new technologies and found that their herd mentality had a significant impact on their first use intentions. Shen et al (2016) found that when consumers and online reviewers have similar educational backgrounds and attitudes, they tend not to pay too much attention to product information, but rather imitate their purchasing decisions and adopt their reviews.…”
Section: Research Model and Hypotheses Developmentmentioning
confidence: 99%
“…Mattke et al (2020) presented that social media platforms can lead to herding behavior. In the context of AI, it is very important to consider herding behavior among group members, as it will affect the acceptance and persistence of the AI task (Darban and Polites, 2020). Herding behavior is a manifestation of herd mentality, which may require mutual learning and knowledge transfer among members (Li et al , 2014).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Although individuals with different characteristics will exhibit varying degrees of conformity (Darban and Polites, 2020), conformity will weaken team diversity to some extent. Intellectual diversity facilitates the establishment of TMS by increasing the professionalism and diversity of team members (Lewis and Herndon, 2011).…”
Section: Artificial Intelligence-related Knowledge Workmentioning
confidence: 99%
“…While prior studies have shed light on the influence of herd behavior in the IS context in different ways, the influence of different types of PI and how they are presented to users is yet to be distinguished and analyzed (e.g. Darban and Polites, 2020; Sun, 2013; Vedadi and Warkentin, 2020).…”
Section: Introductionmentioning
confidence: 99%